Mono-Rhamnolipid Biosurfactants Synthesized by Pseudomonas aeruginosa Detrimentally Affect Colorectal Cancer Cells - Matthew S. Twigg; Simms A. Adu; Suguru Sugiyama; Roger Marchant; Ibrahim M. Banat (MDPI AG, 2022)
Over the past 15 years, glycolipid-type biosurfactant compounds have been postulated as novel, naturally synthesized anticancer agents. This study utilized a recombinant strain of Pseudomonas aeruginosa to biosynthesize a preparation of mono-rhamnolipids that were purified via both liquid and solid-phase extraction, characterized by HPLC-MS, and utilized to treat two colorectal cancer cell lines (HCT-116 and Caco2) and a healthy colonic epithelial cell line CCD-841-CoN. Additionally, the anticancer activity of these mono-rhamnolipids was compared to an alternative naturally derived anticancer agent, Piceatannol. XTT cell viability assays showed that treatment with mono-rhamnolipid significantly reduced the viability of both colorectal cancer cell lines whilst having little effect on the healthy colonic epithelial cell line. At the concentrations tested mono-rhamnolipids were also shown to be more cytotoxic to the colorectal cancer cells than Piceatannol. Staining of mono-rhamnolipid-treated cells with propidium iodine and acridine orange appeared to show that these compounds induced necrosis in both colorectal cancer cell lines. These data provide an early in vitro proof-of-principle for utilizing these compounds either as active pharmaceutical ingredient for the treatment of colorectal cancer or incorporations into nutraceutical formulations to potentially prevent gastrointestinal tract cancer.